In House Training Needs Analysis For Employees - Adhy nursaumi; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2023)
The purpose of this study is to This research is aimed at knowing the provision of job training (in house training) to employees, consistently and continuously guaranteed in quantity, but on the other hand training is needed that is guaranteed in quality. To ensure that the training that will be carried out is in accordance with the needs of the organization, position, and individual employees, so that the quality is guaranteed, a training needs analysis is needed beforehand. This study uses a descriptive qualitative approach with a case study method that uses source triangulation techniques with the objects in the study being all organizational components, both leaders and staff. In data processing, data collection, data reduction, data display, and conclusion and verification are carried out. Research result, revealed that analyzing training needs involves all organizational components. Where, consideration of training needs lies at the level of organization and position. It was concluded that at the individual analysis level it is not used as a basis for determining training needs, so that it is possible for all employees to experience improvement. The results of the study show that in-house training is urgently needed to improve the quality of human resources, efficiency and productivity of employees as a whole.